26 Cardiovascular magnetic resonance activity in the united kingdom: results of the 2014 bscmr survey. (26th April 2015) - Ripley, DP; Sado, DM; McCann, GP; Berry, C
Abstract : Conflicts: Nil Background: The 2011 British Society of Cardiovascular Magnetic Resonance (BSCMR) national survey demonstrated a marked year-on-year increase in the number of CMR scans per centre (2008–2010) and in the total number of CMR scans performed annually in the UK overall. 1 Methods: We undertook the second national survey on behalf of the BSCMR to identify all adult CMR providers within the UK in 2014. The questionnaire was sent to the lead clinician for CMR at each site and electronically reported. Results: Of the 68 adult CMR centres identified in the UK, 55 (81%) responded to the questionnaire. Thirty three (60%) were tertiary cardiac centres and 22 (40%) were district general hospitals. Thirty six hospitals (65%) had a level 3 accredited trainer on site with 559 trainees (87% cardiology) at various levels of training. One hundred and twenty five trainees were at the level 3 stage of training (75% of which were from 5 centres). Thirty three hospitals (60%) had a formal training program for cardiology and 17 (31%) for radiology trainees. The majority of hospitals (44 (80%)) had a quality control program in place. For activity in 2013: 5 centres (9%) provided no details on total numbers of scans, 9 (16%) performed <300 scans, 14 (25%) 300–500, 7 (13%) 501–1000 and 20 (36%) >1000 scans. The total number of reported scans increased by 253% between 2008 (23, 216) and 2013 (58, 936). Mean number of scans per centre are shown in Figure 1 . Conclusion: There is evidence of a sustained increase in CMR service provision in the UK. Most centres provide a CMR training program and quality assurance. Acknowledgements: We would like to thank Drs S. Nair, M. Motwani, V. Ferriera, E. McAlindon, N. Edwards, D. Carrick, M. Goonewardene, A. McDiarmid, A. Uddin, S. Kannoly and H. Douglas for their help with this audit. Reference: Anthony R et al . JCMR 2011;13:57